Pengaruh Keterampilan Komunikasi Bahasa Inggris Terhadap Kinerja Pegawai di Maskapai China Airlines Denpasar Bali - Gilbert, Ryanry; Fatkhurohman Albashori, Muhammad (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This research aims to analyze the influence of English communication skills on employee performance at China Airlines Denpasar Bali. This research uses quantitative research methods. The population of this study was all employees of China Airlines Denpasar Bali, namely 30 people. To determine the sample for this study, a saturated sampling technique was used in which the entire population was sampled in this study. This research data was obtained through a questionnaire which was analyzed using multiple linear regression analysis. The results of the research show that: listening ability (X1) has an influence on employee performance which has a t-count value (2.649) > t table value (2.063) and significant level (0.014) < (0.05). Speaking (X2) has an influence on employee performance which has a calculated t-value (2.512) > t-table (2.063) and a significant level (0.019) < (0.05). Reading (X3) has an influence on employee performance which has a calculated t-value (3.280) > t-table (2.063) and a significant level (0.003) < (0.05). Writing (X4) has no effect on employee performance which has a calculated t-value (0.399) > t-table (2.063) and a significant level (0.693) < (0.05). And simultaneously the variables Listening (X1), Speaking (X2), Reading (X3), and Writing (X4) influence employee performance (Y) which has a calculated F value of (4.926 ) > F table (2.759) and significance level (0.005) < (0.05).